Laparoscopic Radical Resection of Colorectal Cancer in the Treatment of Elderly Colorectal Cancer and Its Effect on Gastrointestinal Function - Liu, Biao; Yao, Chuanhui; Li, Haiying (Frontiers in Surgery, 2022)
[Abstract] Objective To explore the efficacy and safety of laparoscopic radical resection of colorectal cancer in the elderly and its impact on gastrointestinal function. Methods: Methods: A total of 122 elderly patients with colorectal cancer admitted to our hospital from March 2020 to June 2021 were selected as the research objects, and they were divided into the control group (n=61) and the observation group (n=61). The control group was treated with traditional laparotomy, and the observation group was treated with laparoscopic radical resection of colorectal cancer. The clinical data of operation time, incision length, intraoperative bleeding volume, and hospitalization time in the two groups were recorded. Serum motilin (MTL) and gastrin (GAS) levels were measured preoperatively and postoperatively. The duration of abdominal distension, the time for the abdominal sound to return to normal, the time for the anal exhaust to normal, and the time for normal food intake were recorded after operation. The patients were followed up for 6 months postoperatively, and the complications during follow-up were recorded. Results: The operation time, incision length, intraoperative bleeding volume and hospitalization time of the observation group were lower than those of the control group (P<0.05). The duration of abdominal distension, the time for the borborygmus to return to normal, the time for the anus to exhaust gas to normal, and the normal eating time in the observation group were all lower than those in the control group (P<0.05). After surgery, the levels of MTL and GAS in the two groups were lower than those before surgery, and those in the observation group were lower than those in the control group (P<0.05). The total incidence of complications in the observation group (3.28%) was lower than that in the control group (13.12%) (P<0.05). Conclusion: Laparoscopic radical resection of colorectal cancer in the elderly has good effect, short operation time, less trauma, less blood loss during operation, short hospital stay, good recovery of gastrointestinal function, fewer complications and high safety.